2004
DOI: 10.1017/s0263034604223059
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a bright, tunable, ultrafast Compton scattering X-ray source

Abstract: The Compton scattering of a terawatt-class, femtosecond laser pulse by a high-brightness, relativistic electron beam has been demonstrated as a viable approach toward compact, tunable sources of bright, femtosecond, hard X-ray flashes. The main focus of this article is a detailed description of such a novel X-ray source, namely the PLEIADES~Picosecond Laser-Electron Inter-Action for the Dynamical Evaluation of Structures! facility at Lawrence Livermore National Laboratory. PLEIADES has produced first light at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…Another advantage is that the electrons can be precisely synchronized with the driving laser field. In order to further improve the all-optical setup, design parameters for a proof-of-concept experiment have been analyzed in Hartemann et al, 2007. For the calculation of the Compton scattering parameters, a 3D Compton scattering code has been used, which was extensively tested for Compton scattering experiments performed at LLNL Hartemann et al, 2004Hartemann et al, , 2005) (see Sun and Wu, 2011 for an alternative numerical simulation scheme). It is shown that x-ray fluxes exceeding 10 21 s −1 and a peak brightness larger than 10 19 photons/(s mrad 2 mm 2 0.1% bandwidth) can be achieved at photon energies of about 0.5 MeV.…”
Section: A Fundamental Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another advantage is that the electrons can be precisely synchronized with the driving laser field. In order to further improve the all-optical setup, design parameters for a proof-of-concept experiment have been analyzed in Hartemann et al, 2007. For the calculation of the Compton scattering parameters, a 3D Compton scattering code has been used, which was extensively tested for Compton scattering experiments performed at LLNL Hartemann et al, 2004Hartemann et al, , 2005) (see Sun and Wu, 2011 for an alternative numerical simulation scheme). It is shown that x-ray fluxes exceeding 10 21 s −1 and a peak brightness larger than 10 19 photons/(s mrad 2 mm 2 0.1% bandwidth) can be achieved at photon energies of about 0.5 MeV.…”
Section: A Fundamental Considerationsmentioning
confidence: 99%
“…solutions with an exponentially-diverging electron acceleration, even in the absence of an external field (see the books Hartemann, 2001 andRohrlich, 2007 for reviews on these issues).…”
Section: Radiation Reactionmentioning
confidence: 99%
“…T-REX experiments have been already performed on an enhanced version of the 100 MeV LLNL electron linac used for previous Compton scattering sources [2]. The electron bunch is accelerated to ~120 MeV and focused with a series of quadrupole magnets.…”
Section: Nrf Experimentsmentioning
confidence: 99%
“…Several important diffraction measurements were performed with this source, though the results will not be reviewed here. A similar X-ray-generation mechanism is used to produce Compton scattering through electron beam-intense laser interactions (PLADEIS), as described by Hartemann et al [62,63]. Currently, two other FEL operating in the X-ray region are being built, one in Europe (FLASH) and one in Japan.…”
Section: Laser-electron Beam Interactionsmentioning
confidence: 99%